CHARACTERIZATION OF MORTAR WITH PENNISETUM PURPUREUM ASHES AS CEMENT REPLACEMENT MATERIAL - Wan Ibrahim, Mohd Haziman; Al-Fasih, Mohammed Yahya; NIK PA, Nik Nadia Amira; Putra Jaya, Ramadhansyah; Setiawan, Muhammad Ikhsan (IIUM Engineering Journal, 2021)
In this study, the properties of mortar such as standard consistency, setting time, compressive strength, and water absorption rate were investigated. The cement was replaced with Pennisetum purpureum ashes (PPA) in different particle sizes and dosages. PPA was produced in greyish-white ash with total reactive oxides ranging from 37% to 41.1%. Pennisetum purpureum grass (PPG) was burned with a controlled process at 350 °C for the first 3 hours and 600 °C for another 3 hours at a heating rate of 10 °C/min. Then, PPG was ground in three different grinding durations (1, 3, and 6 hours) producing ashes with particle sizes of 10.58 µm, 10.25 µm, and 9.30 µm, respectively. The physical, chemical, and microstructural properties of PPA were evaluated through several tests; particle size analysis, X-ray diffraction analysis, loss on ignition, and chemical composition. Results indicated that PPA is more suitable for use as filling material as a substitute for cement than pozzolanic material as its reactive oxides are less than 50%. The 15% 6H-PPA at 28 days was found to be the optimum PPA replacement dosage and grinding time with cement as it achieved the highest strength and lower water absorption rate among all samples at 7 and 28 days. ABSTRAK: Kajian ini berkenaan sifat mortar seperti konsistensi standard, masa penyediaan, kekuatan menyeluruh, dan kadar penyerapan air. Simen ditukar dengan abu Pennisetum purpureum (PPA) dalam saiz partikel dan sukatan berbeza. PPA pula dihasilkan melalui habuk putih-kekelabuan dengan total reaktif oksida dengan julat purata 37% ke 41.1%. Rumput Pennisetum purpureum (PPG) dibakar dengan proses kawalan pada 350 °C selama 3 jam pertama dan 600 °C pada 3 jam berikutnya pada kadar pemanasan 10 °C/min. Kemudian, PPG dikisar dalam tiga tempoh kisaran berbeza (1, 3, dan 6 jam) menghasilkan abu dengan saiz partikel 10.58 µm, 10.25 µm, dan 9.30 µm, masing-masing. Fizikal, larutan kimia dan sifat struktur mikro PPA telah dikaji melalui pelbagai ujian; analisis saiz partikel, analisis pembelauan X-ray, kehilangan semasa penyalaan dan kandungan kimia. Dapatan kajian menunjukkan PPA adalah lebih sesuai digunakan sebagai material pengisian ganti kepada simen berbanding material pozzolanik kerana reaktif oksida adalah kurang daripada 50%. PPA adalah maksimum pada 15% 6H-PPA selama 28 hari, didapati lebih sesuai sebagai dos pengganti dan masa kisaran bersama simen, kerana kekuatan menyeluruh adalah paling tinggi dan kadar penyerapan air paling kurang antara semua sampel pada 7 dan 28 hari.